0

# Evaluate the integral... Se^(3x)cos(2x)dx S=Integral

Se^(3x)cos(2x)dx  S=Integral

### 2 Answers by Expert Tutors

James R. | PhD Graduate for Physics, Chemistry, Mathematics TutoringPhD Graduate for Physics, Chemistry, Mat...
4.9 4.9 (88 lesson ratings) (88)
1
The first step is to convert the cosine function to the exponential form using Euler's formula.

Cos(2x) = 1/2 * [e^(i2x)-e^(-i2x)]

The next step is to distribute the outside exponential that is 1/2*[e^(3x+i2x)-e^(3x-i2x)].

Now the integral becomes a very simple u and v substitution integral. That is let u = (3+i2)x and v = (3-i2)x therefore du = (3+i2)dx and dv = (3-i2)dx.

Is this far enough help or do you need the next steps?
Kirill Z. | Physics, math tutor with great knowledge and teaching skillsPhysics, math tutor with great knowledge...
4.9 4.9 (174 lesson ratings) (174)
1
You can do it by applying the integration by parts.

∫e3xcos(2x)dx=(½)e3xsin(2x)-(3/2)∫e3xsin(2x)dx=(½)e3xsin(2x)-(¾)e3x(-cos(2x))-(9/4)∫e3xcos(2x)dx

Now let I=∫e3xcos(2x)dx; Then we have an equation:

I=(½)e3xsin(2x)+(¾)e3xcos(2x)-(9/4)I;

Solving for I yields:

I=1/13*[2e3xsin(2x)+3e3xcos(2x)]=e3x/13*[2sin(2x)+3cos(2x)]